Morphology, palaeoecology and taphonomy of the Devonian mitrate Placocystella langei from Paraná Basin, Brazil. Issue 2 (3rd April 2019) - Scheffler, Sandro Marcelo; Horodyski, Rodrigo Scalise; Bosetti, Elvio Pinto
Abstract : Sandro Marcelo Scheffler, Rodrigo Scalise, Horodyski & Elvio Pinto, Bosetti, 2018. Morphology, palaeoecology and taphonomy of the Devonian mitrate Placocystella langei from Paraná Basin, Brazil. Alcheringa 43, 228–240. ISSN 0311-5518. The original holotype and paratypes of the stylophoran mitrate Placocystella langei (Echinodermata) are definitively lost. A neotype is designated here, based on new material collected in the marine Devonian strata of the Apucarana Sub-basin, Paraná, Brazil. Placocystella langei was the first species of Stylophora to be identified in Devonian basins from Brazil. Its range extends from the late Emsian to early Givetian. Taphonomic data indicate that P. langei specimens were preserved in a storm-influenced, transitional offshore environment, and that skeletal remains were few exposed at the water–sediment surface. Considering that the specimens do not exhibit evidence of reworking, it is possible that their final burial was rapid and definitive, which facilitated their almost complete preservation. Finally, taphonomic, diagenetic and sedimentologic data all suggest a shallow infaunal habit for Placocystella langei . Sandro Marcelo Scheffler [schefflersm@mn.ufrj.br ] Departamento de Geologia e Paleontologia, Laborat orio de Paleoinvertebrados (LAPIN), Museu Nacional—UFRJ, Parque Quinta da Boa Vista, s/n, São Cristóvão 20940040, Rio de Janeiro, RJ, Brasil; Rodrigo Scalise Horodyski* [rhorodyski@unisinos.br ] Graduate Program in Geology, Vale do Rio dos Sinos University, Av. Unisinos, 950, Cristo Rei, 93022-000 São Leopoldo, RS, Brasil; Elvio Pinto Bosetti [elviobosetti@gmail.com ] Departamento de Geociências, Universidade Estadual de Ponta Grossa, Av. Carlos Cavalcanti 9.500, Uvaranas, 84010-919, Ponta Grossa, Paran a, Brazil.